PENEGAKAN HUKUM PIDANA TERHADAP TINDAK PIDANASKIMMING(Studi Di Polres Kutai Kartanegara) - Desi Redita Sari; Rini Apriyani; Amsari Damanik (INTELIGENSIA MEDIA, 2023)
The crime of skimming is the theft of debit or credit card information by illegally copying the information on the card's magnetic stripe. In general, ATM skimming crimes are regulated in Article 362 of the Criminal Code (KUHP) and in Article 30 paragraph (1) jo Article 46 paragraph (1) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information. This study aims to analyze law enforcement against skimming offenders in Kutai Kartanegara. The research method used is an empirical approach or socio legal research. The results showed that law enforcement against the perpetrators of skimming crimes at the Kutai Kartanegara Regional Police had not been implemented optimally. In this case, there are still many cases of skimming crimes in the last 4 years that are still in the process of investigation and investigation, so there are still few cases that reach the stage of case settlement. One of the inhibiting factors in law enforcement is the lack of understanding and caution of the public in using ATM cards in making transactions at ATM machines